Entre um e múltiplos Eus: a poesia de Adília Lopes - Dias, Taís Helena Fernandes (2016)
This dissertation intends to analyze the poetic production of Portuguese poet Adília Lopes. Based on poetic procedures, our objective is to outline this poet's project and to capture the configuration of the Self that emanates from her text. The question that arises is: To which extend does Adília Lopes' poetry shape the personal experience of the lyric subject with characters and stories, showing the intimacy that exists between them? How do counter fictional and anti-lyrical technique used in Adília Lopes' poetry reveal a mixed and unstable territory in her writings? To answer this question, we discuss how the Self is built from the historical, philosophical, social, cultural and literary point of view. The theoretical framework regarding the Self in literature can be found in authors, such as Lejeune, Barthes, Nietzsche, Novalis, Friedrich, and others. For the poetic procedure characterization we used critical studies by Rosa Maria Martelo and Flora Süssekind, as well as Adília Lopes' short stories and interviews. Her poetry presents a diversity of Selves, a multitude of voices. Each poem seems to use a poetic procedure and sustains the question of who is actually speaking, whether it is the author, the poet, the author-character or the poet-character